Kinerja Bank Perkreditan Rakyat di Kabupaten Badung Bali Sebelum dan Selama Pandemi Covid-19 - I Wayan Budi Satriya; Ni Komang Sumadi; Sang Ayu Putu Arie Indraswarawati (Juara: Jurnal Riset Akuntansi, 2022)
The financial performance of the banking sector is very important because it can be an early indication of a financial crisis, which can trigger an economic crisis in a country. The purpose of this study was to determine the financial performance of Rural Banks (BPR) in Badung Regency, Bali Province before and during the covid-19 pandemic. BPR financial ratio data for the 2016-2019 period is used as BPR performance data before the covid-19 pandemic, while financial ratios in 2020 are used as BPR performance data during the covid-19 pandemic. The results showed that the CAR ratio increased and differed significantly compared to before the covid-19 pandemic. The NPL ratio also shows an increase and is significantly different compared to before the covid-19 pandemic. The ROA ratio shows a decrease and is significantly different compared to before the covid-19 pandemic. The BOPO ratio shows an increase and is significantly different compared to before the covid-19 pandemic. Meanwhile, the LDR ratio showed an increase but was not significantly different from before the covid-19 pandemic. The change in financial ratios shows a decline in the performance of BPRs in Badung Regency during the covid-19 pandemic.